The Use of Digital Media to Improve Student Activity and Learning Outcomes in Mathematics Learning - Haifani, Maharani Fadhiyah; Ridho, Muhammad Rasyid; Putri, Reza Mareta (Gema Wiralodra, 2025)
This study aims to improve the learning outcomes of grade 2 students of SD Muhammadiyah 4 Kasembon in mathematics lessons in increasing student activation, achievement, and learning completeness using digital media. The subjects of this research are grade 2 elementary school students. Research subjects are used to obtain data on the variables to be studied, so that research can achieve goals and produce quality content. The method used in collecting Digital Game Based Learning (DGBL) data taken during the learning process. The results showed a significant increase in student activeness and learning achievement after the application of digital media, with the level of activeness reaching 75% in the second cycle and the average student score exceeding the Minimum Completion Criteria (KKM). The use of digital media such as interactive videos and educational game applications proved effective in attracting interest in learning, increasing motivation, and helping to understand mathematical concepts. The application of digital media use of Digital Game Based Learning (DGBL) model can attract students' attention and interest in learning, especially mathematics.